Immediate postpartum provision of long-acting reversible contraception. Issue 6 (December 2015) - Goldthwaite, Lisa M.; Shaw, Kate A.
Abstract : Purpose of review: The objective of this review is to describe current literature regarding the role and characteristics of long-acting reversible contraception (LARC) used immediately postpartum. Recent findings: Copper and levonorgestrel intrauterine devices (IUDs) inserted immediately postpartum at the time of both vaginal and cesarean deliveries are associated with higher rates of continuation at 6–12 months when compared with IUDs placed at the postpartum visit (4–8 weeks after delivery), despite higher rates of expulsion. IUDs and contraceptive implants are cost-effective when used immediately postpartum, and they are associated with longer interpregnancy intervals. There is limited evidence regarding the effects of immediate postpartum LARC on breastfeeding. Summary: Use of LARC methods in the immediate postpartum period is both effective and safe, and could reduce unmet need for contraception during this time. More research is needed to explore various immediate postpartum IUD insertion methods and the effects of immediate postpartum progestin-containing LARC on breastfeeding.